ANTIBACTERIAL ACTIVITY OF ZINGIBER OFFICINALE AGAINST FOODBORNE PATHOGENS - Othman, Ahmad Syibli; Azizan, Nurul Alia; Azizan, Nurul Alia; Shambely, Azlin Sham; Mohamad, Noor Ayunie (International Journal of Psychosocial Rehabilitation, 2020)
Zingeber officinale or ginger, used as traditional medicine for over 2,500 years. It has been found to possess a number of pharmachological properties including antimicrobial. The following study was conducted to investigate the antibacterial properties of ginger on foodborne pathogens which are S. aureus, B. cereus, E. coli and S. typhimurium. Screening of antibacterial activity of ethanolic extract of ginger was tested by disc diffusion method using impregnated filter paper with 1000mg/ml concentration of ethanolic extract of ginger on inoculated Mueller Hinton Agar plate. The preliminary screening showed inhibition activity against all tested bacteria. Based on zone sizes, the antibacterial activity was more against gram positive than gram negative bacteria. The Minimum Inhibitory Concentration (MIC) was performed using micro broth dilution test. The MIC of the extract vary between 31.25 and 125 mg/ml and Minimum Bactericidal Concentration (MBC) ranged between 62.5 and 250 mg/ml. S. aureus and B. cereus were more sensitive to extract of ginger, while E. coli and S. typhimurium were not very effective to ginger extract. B. cereus showed the greatest antibacterial effect with MIC value 31.25 mg/ml and MBC value 62.5 mg/ml. Result of this study showed that Z. officinale ethanolic extract had antimicrobial activities against S. aureus, B. cereus, E. coli and S. typhimurium, thus confirming their potentially used as microbial growth inhibitors in the foods and an application as natural antibacterial agent.